William C. Thacker and W. Reid Staton in front of Farmers Cooperative Dairy on North Cherry Street, 1961. - (:unkn) unknown (Forsyth County Public Library)
WSJ 5-21-61 p.D12.
William C. Thacker and W. Reid Staton in front of Farmers Cooperative Dairy on North Cherry Street, 1961.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth